Comparison of aglycon and glycosidic saponin extracts of Cyclamen coum tuber against Candida spp. - Seyedeh Toktam Sajjadi; Azra Saboora; Parisa Mohammadi (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Candidiasis, an important fungal infection, is considered the fourth most common nosocomial blood stream infection. Nowadays, because of increased fungal resistance to antibiotics, the use of herbal medicine has gained particular attention. Cyclamen species are medicinal plants containing triterpenoid saponins, which are shown to have antimicrobial properties. Materials and Methods: Three species of Candida including C. albicans 10231, C. tropicalis 0750, and C. krusei and nine clinical samples were cultured on Sabouraud dextrose agar. Active substances of the tubers were extracted by fractionation method. Susceptibility of Candida to Cyclamen coum tuber extracts was evaluated via minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). Results: Our results demonstrated that ethyl acetate extract had no inhibitory effect on Candida strains, whereas the aqueous and n-butanolic extracts showed considerable activity. MIC and MFC of these extracts varied within the range of 2-32 μg/mL of saponin for different Candida samples. Aglyconic aqueous phase of the extract had the most effective anticandida activity. Glycosidic and aglyconic aqueous extracts were less active on C. albicans strains and C. tropicalis, respectively. Conclusion: Tuber extract of Cyclamen was rich in triterpenoid saponins and had antifungal effect. Sugar chain structure, as well as type and concentration of the aglycones were effective in this activity.